Levels, Dietary Exposure, and Health Risk Estimation of Polycyclic Aromatic Hydrocarbons in Bread Baked with Different Oven and Fuel Types. (2nd January 2023) - Karşı, Melike B. Bayramoğlu; Berberler, Ercan; Kurhan, Şebnem; Bilaloğlu, Köksal; Çakır, İbrahim and Karakaş, Duran
Abstract: The formation and occurrence of EPA priority 16 PAHs in the sourdough bread samples baked in the different ovens and fuel types used in Turkey were discussed. The bread dough prepared in laboratory conditions was baked in 6 commercial bakeries (two of them use firewood and 4 of them use natural gas as fuel), 5 traditional countryside bakeries (firewood as fuel), and 2 household type (electricity) ovens in Bolu Province, Turkey. The most dominantly (<95%) observed PAH compounds were low molecular weight PAHs (2 to 4 ring PAHs). The total content of 16 PAHs in the bread samples were 2.68 ± 3.33, 2.71 ± 3.23, 4.40 ± 1.52, and 3.58 ± 1.74 µg/kg dw, respectively, for the household, countryside, commercial (firewood) and commercial (natural gas) ovens. Sum of carcinogenic PAHs varied between 0.084 ± 0.107 (household ovens) and 0.205 ± 0.240 µg/kg dw (countryside ovens). The ovens using firewood as the heating fuel, countryside and commercial ovens, showed about 2 to 10 times higher marker PAHs (PAH4) levels than the ovens using natural gas (commercial) and electricity (household). The bread samples baked with commercial firewood and household ovens had 1.5 and 2 times higher total TEQ of BaP (0.116 and 0.121 μg/kg dw, respectively) values than that of countryside firewood and commercial natural gas ovens. Estimated incremental lifetime cancer risk (ILCR) results suggested that the consumption of bread baked in four types of ovens may pose no health risk for children and adult consumers.